Ten Years' Experience with the Swiss National Bank's Monetary Policy Strategy - Thomas J. Jordan; Michel Peytrignet; Enzo Rossi (Swiss Journal of Economics and Statistics, 2010)
In December 1999 the Swiss National Bank (SNB) abandoned monetary targeting and introduced a new monetary policy strategy. The cornerstones of the new framework are an explicit definition of what the SNB considers to be price stability, a forecast of inflation over a three-year horizon, and a target range for the three-month Swiss franc Libor. The strategy lived up to expectations in every respect and contributed to strengthening the SNB's credibility. In particular, the new framework's flexibility proved successful in times of financial stress. The term reference interest rate contains an automatic monetary stabilizer that has insulated the nonfinancial sector from much of the turbulence. The major challenge lying ahead is sustained accuracy in the assessment of future inflation.
Keywords: E5; 330; Monetary policy strategy; inflation targeting; monetary policy rules; inflation forecasts; financial crisis; unconventional monetary policy